We know that
Rigid transformation:
A rigid transformation (also called an isometry) is a transformation of the plane that preserves length.
Reflections, translations, rotations, and combinations of these three transformations are "rigid transformations"
so, it's length must be preserved
now, we will check each option
option-A:
we have (x,3y)
y-value changes but x-value will remain same
It changes length
so, this is not rigid transformation
option-B:
we have (3x,y)
x-value changes but y-value will remain same
It changes length
so, this is not rigid transformation
option-C:
(2x, y+2)
It changes length of x-value
but it is only shifting y-value
so, it changes length
so, this is not rigid transformation
option-D:
Both shifts values
but it's length will always be same
so, this is rigid transformation..............Answer
Answer:
goes into the box
Step-by-step explanation:
Let the number be
, then
![(m^x)^{\frac{1}{3}}=m^{-12}](https://tex.z-dn.net/?f=%28m%5Ex%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%3Dm%5E%7B-12%7D)
We now use the following property of exponents to simplify the left hand side of the equation.
![(a^m)^n=a^{mn}](https://tex.z-dn.net/?f=%28a%5Em%29%5En%3Da%5E%7Bmn%7D)
This implies that;
![m^{x\times \frac{1}{3}}=m^{-12}](https://tex.z-dn.net/?f=m%5E%7Bx%5Ctimes%20%5Cfrac%7B1%7D%7B3%7D%7D%3Dm%5E%7B-12%7D)
![\Rightarrow m^{\frac{x}{3}}=m^{-12}](https://tex.z-dn.net/?f=%5CRightarrow%20m%5E%7B%5Cfrac%7Bx%7D%7B3%7D%7D%3Dm%5E%7B-12%7D)
Since the bases are the same, we equate the exponents to get;
![{\frac{x}{3}=-12](https://tex.z-dn.net/?f=%7B%5Cfrac%7Bx%7D%7B3%7D%3D-12)
We now multiply both sides by 3 to get;
![\frac{x}{3}\times 3=-12\times 3](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B3%7D%5Ctimes%203%3D-12%5Ctimes%203)
![\Rightarrow x =-36](https://tex.z-dn.net/?f=%5CRightarrow%20x%20%3D-36)
Therefore the number that goes into the box is ![-36](https://tex.z-dn.net/?f=-36)
It's the first one you can just add or multiply the expressions to get the answer
7 + 2p = p
subtract 2p on both sides. it now leaves you with:
7= -p
divde both sides by -1.
-7 = p